2021
DOI: 10.3390/biom11050614
|View full text |Cite
|
Sign up to set email alerts
|

Custard Apple (Annona squamosa L.) Leaves: Nutritional Composition, Phytochemical Profile, and Health-Promoting Biological Activities

Abstract: Annona squamosa L. (custard apple) belongs to the family Annonaceae and is an important tropical fruit cultivated in the West Indies, South and Central America, Ecuador, Peru, Brazil, India, Mexico, the Bahamas, Bermuda, and Egypt. Leaves of custard apple plants have been studied for their health benefits, which are attributed to a considerable diversity of phytochemicals. These compounds include phenol-based compounds, e.g., proanthocyanidins, comprising 18 different phenolic compounds, mainly alkaloids and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 66 publications
3
47
0
1
Order By: Relevance
“…Crude protein (%) = (mL standard acid × N of acid) − (mL blank × N of base) − (mL std base × N of base) × 1 : 4007 Weight of sample in grams × 100 (5) where, N = normality, and percentage of crude protein was obtained by multiplying the nitrogen value by a factor of 6.25%. Crude protein = Nitrogen in sample × 6.25.…”
Section: Determination Of Crude Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Crude protein (%) = (mL standard acid × N of acid) − (mL blank × N of base) − (mL std base × N of base) × 1 : 4007 Weight of sample in grams × 100 (5) where, N = normality, and percentage of crude protein was obtained by multiplying the nitrogen value by a factor of 6.25%. Crude protein = Nitrogen in sample × 6.25.…”
Section: Determination Of Crude Proteinmentioning
confidence: 99%
“…The usage of essential oils is attracting significant attention, as these oils are a good source of various bioactive components. They are nowadays chosen over chemical antioxidants because of their antioxidant and antibacterial characteristics, and also due to their generally recognized as safe (GRAS) nature [ 5 , 6 ]. Essential oils are mostly made up of terpenes produced by the mevalonate pathway, which are complex combinations of volatile chemicals found in aromatic plants.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that the documentation of ethnobotanical knowledge and ethnomedicinal plants can play a significant role in the conservation of traditional ethnobotanical knowledge and the protection of threatened ethnomedicinal plants [ 28 , 29 , 30 , 31 ]. The Himalayan forests provided a rich reservoir of medicinal plants that are essential to the native community [ 32 , 33 ]. Various studies on medicinal plants used by tribal groups in India have found that they prefer traditional medicine since it is less expensive, has fewer side effects, and is a part of their lives and culture on which our findings are set up.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, new and effective treatments to prevent the development of oral cancer are required. In recent years, several authors have reported the potential of natural products and phytochemicals derived from plants in the treatment of oral diseases [ 7 , 8 , 9 , 10 , 11 ]. Several natural compounds have been investigated for their ability to cause apoptosis in human cancer cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%